RE[CREATE]tion : revealing the agency of recreational spaces in the township of Mamelodi East through architecture as a 'dispositif' for the everyday - Devenish, Paul (University of Pretoria, 2022)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2021.